Validation of urine colour L*a*b* for assessing hydration amongst athletes - Feng, Yiwei; Fang, Guoliang; Qu, Chaoyi; Cui, Shuqiang; Geng, Xue; Gao, Derun; Qin, Fei; Zhao, Jiexiu (Frontiers in Nutrition, 2022)
Objectives: Existing studies have confirmed that urine colour through a urine colour chart is one of the effective indicators for assessing hydration. In recent years, the L*a*b* colour space has been widely used in the objective quantitative analysis of colour. The L*, a* and b* values represent the luminance change from black to white, the chromaticity change from green to red and the chromaticity change from blue to yellow, respectively. This study aimed to examine the validity of the urine colour L*a*b* parameters for assessing the level of hydration amongst athletes. Methods: The study included a total of 474 young elite athletes (251 males and 223 females, age: 24.59 ± 4.86 years). A total of 803 urine samples were collected from the subjects in various stages of hydration, including morning urine and spot urine sample during rehydration. L*a*b* parameters were measured by spectrophotometer. Hydration status was assessed via urine osmolality and urine specific gravity. Results: Urine colour b* value has a high correlation with urine specific gravity and urine osmolality (r = 0.811, 0.741, both p < 0.01); L* value has a moderate correlation with urine specific gravity and urine osmolality (r = -0.508, -0.471, both p < 0.01); there was no significant correlation between a* value and urine specific gravity, urine osmolality (p > 0.05). Whether the diagnosis of hypohydration is based on Usg ≥ 1.020 or Uosm ≥ 700 mmol/kg: The AUC of b* values were all above 0.9 and the specificity and sensitivity of b* values were high (both greater than 80%). The AUC of both L* and a* values were less than 0.5. Whether the diagnosis of hyperhydration is based on Usg ≤ 1.010 or Uosm ≤ 500 mmol/kg: The AUC of b* values were all above 0.9 and the specificity and sensitivity of b* value were high (both greater than 90%). The AUC of both L* and a* values were less than 0.5. Conclusion: These results suggested that the validity of urine colour b* value for assessing hydration amongst athletes was high, however, the validity of urine colour L* and a* values were low.